Analysis of the Study of Midwifery Care for Malnourished Toddlers at the Linge Health Center, Central Aceh Regency, Indonesia - Dewi, Nova Ratna; Sri Wahyuni MS; Hidayana (HM Publisher, 2024)
Malnutrition among toddlers is still a public health problem in Indonesia, including in Central Aceh Regency. Comprehensive and quality midwifery care is very important to help malnourished toddlers achieve optimal nutritional status. This study aims to analyze the study of midwifery care for malnourished toddlers at the Linge Health Center, Central Aceh Regency, Indonesia. This research uses a case study design with a qualitative approach. Data was collected through in-depth interviews with midwives, observation, and documentation of midwifery care. The study shows that midwifery care for malnourished toddlers at the Linge Health Center is quite good. Midwives have carried out assessment, diagnosis, intervention and evaluation using midwifery care standards. Midwifery care for malnourished toddlers at the Linge Health Center is quite good, but still needs to be improved by increasing mothers' knowledge about nutrition, strengthening coordination between sectors, and increasing resources.